Relation of MRI‐Detected Features of Patellofemoral Osteoarthritis to Pain, Performance‐Based Function, and Daily Walking: The Multicenter Osteoarthritis Study. Issue 2 (18th November 2021) - Maxwell, J. L.; Neogi, T.; Crossley, Kay M.; Macri, Erin M.; White, Dan; Guermazi, A.; Roemer, F. W.; Nevitt, M. C.; Lewis, C. E.; Torner, J. C.; Stefanik, J. J.
Abstract : Objective: The study objective was to determine the relationship of magnetic resonance imaging (MRI)‐detected features of patellofemoral joint osteoarthritis to pain and functional outcomes. Methods: We sampled 1, 099 participants from the 60‐month visit of the Multicenter Osteoarthritis Study (mean ± SD age: 66.8 ± 7.5 years; body mass index: 29.6 ± 4.8; 65% female). We determined the prevalence of MRI‐detected features of patellofemoral joint osteoarthritis (eg, cartilage damage, bone marrow lesions, and osteophytes) and assessed the relationship between these features and knee pain severity, knee pain on stairs, chair stand time, and walking less than 6, 000 steps per day. We evaluated the relationship of MRI features to each outcome using logistic and linear regression, adjusting for potential covariates. Results: Participants with cartilage damage in 3‐4 subregions had the highest mean pain severity (22.0/100; 95% confidence interval [CI]: 17.6‐26.4 mm). They also showed higher odds of having at least mild pain on stairs (odds ratio [OR]: 3.3; 95% CI: 1.7‐6.5) and of walking less than 6, 000 steps per day (OR: 2.3; 95% CI: 1.1‐4.4) compared with those without cartilage damage. Participants with bone marrow lesions in 3‐4 subregions had higher odds of at least mild pain on stairs than those without (OR: 3.3; 95% CI: 2.2‐5.2). Participants with osteophytes in 3‐4 subregions also had higher odds of walking less than 6, 000 steps/day (OR 2.1, 95% CI: 1.3‐3.5, respectively). Conclusion: MRI‐detected features of osteoarthritis of the patellofemoral joint are related to pain and functional performance. This knowledge highlights the need to develop treatments for those with patellofemoral joint osteoarthritis to improve pain and maximize function.